English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

math 112

2007-01-15 13:05:29 · 10 answers · asked by Anonymous in Science & Mathematics Mathematics

10 answers

Make the substitution y = x^2, reducing this to y^2 - 2y + 1 = 0. Does that look a lot easier? :)

2007-01-15 13:10:13 · answer #1 · answered by Anonymous · 0 0

First: factor the expression - multiply the 1st and 3rd coefficient to get 1. Find two numbers that give you 1 when multiplied and -2 (2nd-middle coefficient) when added/subtracted. The numbers are -1, -1

Sec: rewrite the expression with the new middle numbers... when you have 4 terms - group "like" terms...

(x^4 - x^2) - (x^2 + 1) = 0

x^2(x^2 - 1) - 1(x^2 - 1) = 0

(x^2 - 1)(x^2 - 1) = 0

(x^2 - 1)^2 = 0

Third: eliminate the exponent >find the square root of both sides...

V`(x^2 - 1)^2 = V`0
x^2 - 1 = 0

*Add 1 to both sides...

x^2 - 1 + 1 = 0 + 1
x^2 = 1

*Square both sides...

V`x^2 = +/- V`1
x = -1, 1

2007-01-15 21:24:34 · answer #2 · answered by ♪♥Annie♥♪ 6 · 0 0

solve x^4-2x^2+1=0?
Put x^2=y, then the above Eq. becomes:
y^2 -2y+1=0 or (y-1)^2=0 which leads to y=1
or x^2=1 or
x= +1 or -1Answer.

2007-01-15 21:14:22 · answer #3 · answered by Anonymous · 0 0

x^4 - 2x^2 + 1 = 0
Factorizing
(x^2)^2 - 2. x^2 . 1 + 1^2 = 0
(x^2 - 1)^2 = 0
[(x + 1)(x - 1)]^2 = 0
Solve for x
x = -1, -1, 1, 1

2007-01-15 21:12:34 · answer #4 · answered by Sheen 4 · 1 0

t = x^2 , t>=0
t^2 - 2t + 1=0
<=> t = 1
<=> x^2 = 1
<=> x = +-1

2007-01-15 21:11:44 · answer #5 · answered by James Chan 4 · 1 0

Here is my complete solution
(x^2-1)(x^2+1) = 0
(x-1)(x+1)(x^2+1) = 0
x = 1 or x = 1

2007-01-15 21:14:23 · answer #6 · answered by Anis Z 1 · 0 0

x^4-2x²+1=0 ==> x^4 = y²

y² - 2y + 1 = 0
d = -2² - 4.1.1
d = 4 - 4
d = 0

y = (2 +/- 0) : 2
y' = y" = 2:2 = 1
y"' = y"" = \/1 = 1
Answer:
x^4 = 1
<>

2007-01-15 21:18:08 · answer #7 · answered by aeiou 7 · 0 0

unsolvable because 2+1 not = 0
if it could be 0 then anything to the 0 power is 1 and x to the 1st power is x

2007-01-15 21:14:15 · answer #8 · answered by ? 2 · 0 1

x={1,-1}

2007-01-15 21:10:21 · answer #9 · answered by abcde12345 4 · 0 0

the farthest i got was:
(x*x*x*x)-(2x*2x)=1

2007-01-15 21:10:41 · answer #10 · answered by WaitingForAnswers 2 · 0 2

fedest.com, questions and answers